No More "Local" Insurrection or Terrorism: The Dark Side of the Cobweb. Issue 2 (3rd April 2018) - Chan, Stephen
Abstract : World Society was the leitmotif of John Groom. It was a pluralist vision of International Relations set against Realism and state hegemonies. In this, it sought to establish an enhanced pluralism, citizen organisation and action, as a norm. It was a prescient forerunner of what we now commonly recognise as international civil society. Groom's other resonant work on third-party and Track II mediation—citizen agency and intervention on behalf of norms of shared needs and equality—was an expression of that. However, all this took place within the context of an interlinked world system described as a cobweb. Not only did this model fail to predict the spiders and slaughter in today's cobweb, it shared an Enlightenment view of civil society as secular. This paper talks about religious spiders and the sort of atrocious but anti-hegemonic pluralism that is now vexatiously glued to all we do internationally. However, the paper recognises that, reconfigured, Groom's work laid first foundations for today's International Relations.